Dokumentalne etiudy szkolne lat 50. i 60. - Mąka-Malatyńska, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The subject of the article are the poetics of films made in the Lodz Film School in the first years of its existence. Analysis of selected films allows us to trace the metamorphoses of documentary forms which were sometimes parallel to changes being observed in mainstream documentaries, sometimes preceding them, sometimes imitating them. Documentary school films from this period illustrate one of the most important phenomena in the history of Polish documentary cinema: the transition from a persuasive document to an observation film whose poetics are the basis for defining the documentary in Poland.